A study of clinico-epidemiological and dermoscopic patterns of vitiligo in pediatric age group - Sneha Gandhi; Murugesh Shamanur; A R Shashikiran; Mamatha Kusagur; Sugareddy; Vijay Bhaskar (Indian Journal of Paediatric Dermatology, 2017)
Context: Childhood vitiligo although similar to adult vitiligo has several distinct epidemiological, clinical, therapeutic and prognostic profile when compared with adult onset vitiligo. Aims: This study was conducted in an attempt to ascertain the clinico-epidemiological profile of patients in pediatric vitiligo patients (<18 years) and to conduct a dermoscopic analysis of the vitiligo patches. Subjects and Methods: This study was designed to study the clinic-epidemiological characteristics of childhood vitiligo between July 2015 and December 2015. A total of eighty childhood vitiligo patients were examined. In addition, 160 patches were studied for dermoscopic patterns to correlate with clinical stability and pattern of pigmentation. Results: Female to male ratio was 2.2:1. Average duration of the disease was 2.2 years. The mean age of onset was 7.6 years. A positive family history was seen in 18 patients. The pattern of viltigo in descending order of frequency was vitiligo vulgaris, segmental distribution, focal vitiligo, and acral vitiligo. The most common site was trunk. Dermatological associations were, history of atopy in 32 patients, alopecia aearata (1 patient) halo nevi (1 patient), and lichen nitidus (1 patient). The dermoscopic features of disease activity in order of frequency in our study were as follows: Trichrome pattern, nebulous pattern, star burst pattern, comet tailing of the lesion, and amoeboid pattern. 69 patients (43.12%) showed leukotrichia on dermoscopy, 74 (46.25%) showed perifollicular pigmentation, 32 patients (20%) showed marginal pigmentation, 26 (16.25%) showed both patterns whereas the rest did not show the signs of repigmentation. Under ultraviolet light examination, a diffuse white glow was seen in 147 (91.87%) of the patients. Conclusions: Vitiligo prevalence among children is on the rise and clinicoepidemiological data on this disease in between far and few. We found that dermoscopy was able to pick up disease activity earlier than the clinical onset of disease instability. This is the first study analyzing the dermoscopic pattern in pediatric vitiligo to the best of our knowledge.